Interactive training course to develop information and communication competences in sport school coaches - Polyak, D. A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to test benefits of a new interactive training course, complementary to the advanced training system, to develop information communication competences and skills in the sport school coaches.